Trends in Labor Induction in the United States, 1989 to 2020. Issue 4 (July 2022) - Simpson, Kathleen Rice
Abstract : The rate of induction of labor in the United States has risen sharply over the last several years as compared to a slow steady increase since 1989 when these data first began to be collected on United States standard certificates of live birth. The rising rate of induction of labor in the United States has significant implications for nurse staffing for maternity units and for patient safety.